Globally regional life cycle analysis of automotive lithium-ion nickel manganese cobalt batteries - Kelly, Jarod C.; Dai, Qiang; Wang, Michael (Mitigation and adaptation strategies for global change, 2020)
Electric vehicles based on lithium-ion batteries (LIB) have seen rapid growth over the past decade as they are viewed as a cleaner alternative to conventional fossil-fuel burning vehicles, especially for local pollutant (nitrogen oxides [NO x ], sulfur oxides [SO x ], and particulate matter with diameters less than 2.5 and 10 μm [PM 2.5 and PM 10 ]) and CO 2 emissions. However, LIBs are known to have their own energy and environmental challenges. This study focuses on LIBs made of lithium nickel manganese cobalt oxide (NMC), since they currently dominate the United States (US) and global automotive markets and will continue to do so into the foreseeable future. The effects of globalized production of NMC, especially LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC111), are examined, considering the potential regional variability at several important stages of production. This study explores regional effects of alumina reduction and nickel refining, along with the production of NMC cathode, battery cells, and battery management systems. Of primary concern is how production of these battery materials and components in different parts of the world may impact the battery’s life cycle pollutant emissions and total energy and water consumption. Since energy sources for heat and electricity generation are subject to great regional variation, we anticipated significant variability in the energy and emissions associated with LIB production. We configured Argonne National Laboratory’s Greenhouse gases, Regulated Emissions, and Energy use in Transportation (GREET®) model as the basis for this study with key input data from several world regions. In particular, the study examined LIB production in the US, China, Japan, South Korea, and Europe, with details of supply chains and the electrical grid in these regions. Results indicate that 27-kWh automotive NMC111 LIBs produced via a European-dominant supply chain generate 65 kg CO 2 e/kWh, while those produced via a Chinese-dominant supply chain generate 100 kg CO 2 e/kWh. Further, there are significant regional differences for local pollutants associated with LIB, especially SO x emissions related to nickel production. We find that no single regional supply chain outperforms all others in every evaluation metric, but the data indicate that supply chains powered by renewable electricity provide the greatest emission reduction potential.